PENDIDIKAN SENI: PERGULATAN SUATU MAKNA - Laksono, Kardi (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2013)
The very fact that painting was for Leonardo such an axtraordinary synthesis of different elements brings him closer o nature, in that he claims for the painter the role of universal being and the ability to use the creative impulse to mirror nature, which then approaches divine necessity. Naturally, when we look at one of Leonardo’s paintings, we should think of a kind of – it’s not a contradiction – of contrivance, of a painting that’s a synthesis between very different things. For him painting is a philosophy, a science, it’s a mental process and in every picture, just as in every page of his manuscripts, we can find an infinite number of hints about relationship and references. These relationship and references are also demonstrated by a number of philosophers through their thoughts about art and esthetics.